African domestic supply booms in value chains of fruits, vegetables, and animal products fueled by spontaneous clusters of SMEs - Reardon, Thomas; Liverpool-Tasie, Lenis Saweda O.; Belton, Ben; Dolislager, Michael; Minten, Bart; Popkin, Barry; Vos, Rob (Wiley, 2024)
There is an international consensus that Africans consume less fruits and vegetables (FV), and animal products (AP) than they need for adequate nutrition, and that production and supply chains of these products are constrained. Yet, in this paper, we show that despite these problems, there is a lot of dynamism in demand and supply of these nutrient-dense products in Africa: (1) macro evidence of “domestic supply booms"—with supply growing as fast as or faster than in Asia and Latin America; (2) only 2–4% of FV, and 10% of AP consumption in Africa is imported, and only about 1–2% of the output of FV and AP is exported: the supply booms have thus been overwhelming domestically sourced, not imported; (3) micro evidence of substantial shares of consumption of FV and AP in total food consumption, similar to Asia's; (4) evidence of rapid development of spontaneous clusters of farms and off-farm SMEs (output wholesalers, logistics, processors, and agro-dealers supporting farmers). These clusters are important in fueling the supply booms. Illustrative cases from Ethiopia, Nigeria, Tanzania, and Zambia are presented. We recommend that African governments and international partners: (1) internalize the fact that these spontaneous clusters are forming and already fueling supply booms; (2) note that important drivers of the booms have been government investments in wholesale markets, roads, and other infrastructure like electrification, and agricultural research/extension; (3) leverage and support existing spontaneous clusters and help new ones to form by greatly increasing those three types of public investments.